Cardiac effects of dapagliflozin in diabetic rats with subacute exposure - ERCAN, FERİHA (My University, 2022)
Background and Aims: Dapagliflozin (DAPA) is a sodium-glucose co-transporter 2 (SGLT2) inhibitor used for the treatment of type 2 diabetes mellitus (T2DM) as a monotherapy or combination therapy with other antidiabetic medicines. The Food and Drug Administration (FDA) recently approved DAPA to minimize the risk of hospitalization due to heart failure in patients with T2DM because of its antihypertensive and antihyperglycemic activities. However, further study of DAPA is necessary to ensure the safety of patients.
Keywords: Temel Eczacılık Bilimleri; Sağlık Bilimleri; Eczacılık; Yaşam Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Health Sciences; Pharmacology and Therapeutics; Life Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacology; General Pharmacology, Toxicology and Pharmaceutics; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Pharmacology (medical); Pharmacy; Drug Guides; Dapagliflozin; SGLT2 inhibitor; Type 2 diabetes mellitus; Cardio-protection; GLUCOSE COTRANSPORTER 2; OXIDATIVE STRESS; SGLT2 INHIBITOR; TROPONIN-T; CARDIOMYOPATHY; DIET; Dapagliflozin; SGLT2 inhibitor; Type 2 diabetes mellitus; Cardio-protection